The Role of Hospital and Community Pharmacists in the Management of COVID-19: Towards an Expanded Definition of the Roles, Responsibilities, and Duties of the Pharmacist - Nicola Luigi Bragazzi; Muhammad Mansour; Alessandro Bonsignore; Rosagemma Ciliberti (MDPI AG, 2020)
Since late December 2019, a novel, emerging coronavirus was identified as the infectious agent responsible for a generally mild but sometimes severe and even life-threatening disease, termed as "coronavirus disease 2019" (COVID-19). The pathogen was initially named as "2019 novel coronavirus" (2019-nCoV) and later renamed as "Severe Acute Respiratory Coronavirus type 2" (SARS-CoV-2). COVID-19 quickly spread from the first epicenter, the city of Wuhan, province of Hubei, mainland China, into neighboring countries, and became a global pandemic. As of July 15th 2020, the outbreak is still ongoing, with SARS-CoV-2 affecting 213 countries and territories. The coronavirus has caused a dramatic toll of deaths and imposed a severe burden, both from a societal and economic point of view. COVID-19 has challenged health systems, straining and overwhelming healthcare facilities and settings, including hospital and community pharmacies. On the other hand, COVID-19 has propelled several changes. During the last decades, pharmacy has shifted from being products-based and patient-facing to being services-based and patient-centered. Pharmacies have transitioned from being compounding centers devoted to the manipulation of materia medica to pharmaceutical centers, clinical pharmacies and fully integrated "medical-pharmaceutical networks", providing a significant range of non-prescribing services. Moreover, roles, duties and responsibilities of pharmacists have paralleled such historical changes and have known a gradual expansion, incorporating new skills and reflecting new societal demands and challenges. The COVID-19 outbreak has unearthed new opportunities for pharmacists: community and hospital pharmacists have, indeed, played a key role during the COVID-19 pandemic, suggesting that a fully integrated, inter-sectoral and inter-professional collaboration is necessary to face crises and public health emergencies. Preliminary, emerging evidence seems to suggest that, probably, a new era in the history of pharmacies ("the post-COVID-19 post-pharmaceutical care era") has begun, with community pharmacists acquiring more professional standing, being authentic heroes and frontline health workers.